Research on absorption spectroscopy of CH4 around 1.315 μm - Shao, Jie; Gao, Xiaoming; Deng, Lunhua; Huang, Wei; Yang, Yong; Pei, Shixi; Yuan, Yiqian; Zhang, Weijun (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Measurements have been made about the absorption features of CH4 around 1.315 μm by using the second harmonic detection technique of tunable diode laser with multipass cell (white). Studies concerning the second harmonic detection technique of CH4 around 1.65 μm have been widely reported currently, but reports about the absorption features in NIR spectra of CH4 around 1.315 mm can scarcely be found. We have performed a detailed study about the absorption features of CH4 around 1.315 μm and we present the results here. We give the line positions, the line intensities and self-broadening coefficients near 1.315 μm at a pressure of 0.077 torr.
Optica Applicata, Vol. 35, 2005, nr 1, s. 155-162
Keywords: optyka; modulation spectroscopy; diode lasers; the second harmonic detection